The Short-Term Retention of Depth - Adam Reeves; Jiehui Qian (Vision, 2021)
We review research on the visual working memory for information portrayed by items arranged in depth (i.e., distance to the observer) within peri-personal space. Most items lose their metric depths within half a second, even though their identities and spatial positions are retained. The paradoxical loss of depth information may arise because visual working memory retains the depth of a single object for the purpose of actions such as pointing or grasping which usually apply to only one thing at a time.